Journal of Experimental Criminology - Mazerolle, Lorraine; Wilson, David B.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The Journal of Experimental Criminology focuses on high quality experimental and quasi-experimental research in the advancement of criminological theory and/or the development of evidence based crime and justice policy. The journal is also committed to the advancement of the science of systematic reviews and experimental methods in criminology and criminal justice. The journal seeks empirical papers on experimental and quasi-experimental studies, systematic reviews on substantive criminological and criminal justice issues, and methodological papers on experimentation and systematic review. The journal encourages submissions from scholars in the broad array of scientific disciplines that are concerned with criminology as well as crime and justice problems.
Keywords: Political science; Social sciences; Criminology and Criminal Justice, general; Political Science; Social Sciences, general